(untitled) (ELS Journal on Interdisciplinary Studies in Humanities, 2025)
This paper investigates the use of conceptual metaphors in the Farewell Sermon of Prophet Muhammad (PBUH) using the framework of Conceptual Metaphor Theory (CMT). Drawing from discourse analysis and cognitive linguistics, the study categorizes metaphors into structural, ontological, and orientation types, revealing how abstract theological and moral concepts are conveyed through culturally grounded metaphors. The findings highlight the cognitive strategies embedded in prophetic discourse and their enduring rhetorical power. The study contributes to both metaphor research and Islamic linguistic heritage by offering a deeper understanding of how abstract Islamic teachings are made accessible and memorable through metaphor. This research bridges cognitive linguistics and Islamic studies by analyzing how abstract moral and theological concepts are conveyed metaphorically. It contributes to understanding how religious discourse uses metaphor to make abstract principles tangible and relatable, reinforcing moral and spiritual instruction. Conceptual Metaphor Theory (CMT), introduced by (Lakoff & Johnson, 1980), proposes that metaphor is not just a figure of speech but a fundamental mechanism of human cognition. Metaphors map concepts from a familiar source domain to a more abstract target domain, shaping thought, language, and behavior.